Participation modes and diplomacy of Gulf Cooperation Council (GCC) countries towards the global sustainability agenda. Issue 5 (4th July 2019) - Al-Saidi, Mohammad; Zaidan, Esmat; Hammad, Suzanne
ABSTRACT: After decades of reluctance, the Gulf Cooperation Council (GCC) countries are now more engaged within the global sustainability agenda. Though they historically sought to coordinate strategies, differences in environmental diplomacy and participation modes currently exist. This article examines these differences and links diplomacy to political and economic considerations during different eras. It maps positions, activism in multilateral agreements, and investigates recent changes in light of increased domestic pressures and the rise of formalised national visions. The increased global environmental engagement of GCC countries can yield better outcomes, but environmental pillars do not feature highly in their current visions.